Commentary on "How Stable is Pitch Labeling Accuracy in Absolute Pitch Possessors?" by W. Gruhn, R. Ristmägi, P. Schneider, A. d'Souza, & K. Kiilu - Schlemmer, Kathrin Bettina (Empirical Musicology Review, 2019)
This paper is a brief commentary on the paper "How stable is pitch labeling accuracy in absolute pitch possessors" by W. Gruhn, R. Ristmägi, P. Schneider, A. d'Souza, and K. Kiilu. The original paper presents evidence for the influence of timbre on the pitch labeling accuracy of absolute pitch (AP) possessors. The presented data result from a solid methodology and show a clear pitch labeling accuracy drop from instrumental timbres to sinusoidal tones, with manipulated sounds being in the middle. The commentary underlines the view that the presented results are compatible with a memory perspective on AP and can be interpreted as evidence for the influence of training on the development of AP.